Light-induced surface patterning of alumina. Issue 34 (27th May 2020) - Choi, Jaeho; Kang, Hong Suk; Jo, Wonhee; Kim, Hee-Tak
Abstract : This work presents a new alumina-patterning platform that uses a photo-reconfigurable azobenzene–alumina composite as an imprinting material. Abstract : Micro/nano-patterned alumina surfaces are important in a variety fields such as chemical/biotechnology, surface science, and microelectro-mechanical systems. However, for patterning alumina surfaces, it still remains a challenge to have a lithographic tool that has large flexibility in design layouts, structural reconfigurability, and a simple fabrication process. In this work, a new alumina-patterning platform that uses a photo-reconfigurable azobenzene–alumina composite as an imprinting material is presented. Under far-field irradiation, the azobenzene–alumina anisotropically flows in the direction parallel to the light polarization. Accordingly, an arbitrarily designed azobenzene–alumina composite by imprinting can be deterministically reconfigured by light polarization and irradiation time. The photo-reconfigured azobenzene–alumina is then converted to pure alumina through calcination in an air atmosphere, which provides thin crack-free alumina patterns with a high structural fidelity. The novel combination of photo-reconfigurable azobenzene moieties and an alumina precursor for imprinting the material provides large flexibility in designing and controlling geometric parameters of the alumina pattern, which potentially offers significant value in various micro/nanotechnology fields.